Engineering documentation control/configuration management standards manual :bpolicies, procedures, flow diagrams, forms and form instructions for product manufacturing companies - Watts, Frank B. (John Wiley & Sons, Inc., 2018)
Describes the best of the best management practices for the configuration management processes